2017
DOI: 10.1016/j.chembiol.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

One Enzyme, Three Metabolites: Shewanella algae Controls Siderophore Production via the Cellular Substrate Pool

Abstract: Highlights d AvbD is the key player in the biosynthesis of the siderophore avaroferrin d Multispecificity leads to three native products: avaroferrin, putrebactin, and bisucaberin d Enzyme kinetics discriminate the two native substrates in favor of bisucaberin d The cellular substrate pool shifts siderophore production toward avaroferrin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 37 publications
(52 reference statements)
4
43
0
Order By: Relevance
“…Since the heterodimer 4 is produced in lower amounts than 3 in X. budapestensis , the amount of HC might be the limiting factor in the biosynthesis and the reason why no bisucaberin was detected. Indeed, for Shewanella algae B516 it was shown that product formation is driven by the available substrate pool of the precursors HC and HP (Rütschlin et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Since the heterodimer 4 is produced in lower amounts than 3 in X. budapestensis , the amount of HC might be the limiting factor in the biosynthesis and the reason why no bisucaberin was detected. Indeed, for Shewanella algae B516 it was shown that product formation is driven by the available substrate pool of the precursors HC and HP (Rütschlin et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Astrain of Shewanella algae whichwas co-isolated with V. alginolyticus from the same seaweed sample evaded this siderophore piracy by producing avaroferrin (41)( Figure7a)-a chimera of the homodimeric macrocyclic hydroxamate siderophores putrebactin and bisucaberin. [148] In ad isc-diffusion assay on agar,a varoferrin (50 nmol) led to the formation of az one with inhibited swarming motility of V. alginolyticus whereas the homodimerics iderophores were considerably lessactive. [149] Other siderophores were inactive (> 500 nmol), whereas deferasirox,a na rtificially optimized iron chelator for which no receptor in V. alginolyticus is available wasapotent swarming inhibitor like avaroferrin.…”
Section: Interspecies Competition and The Microbiotamentioning
confidence: 99%
“…To sequester ferric iron from the environment, V. alginolyticus encodes many different iron‐siderophore receptors in its genome that allow the bacterium to engage in piracy of siderophores produced by other species. A strain of Shewanella algae which was co‐isolated with V. alginolyticus from the same seaweed sample evaded this siderophore piracy by producing avaroferrin ( 41 ) (Figure a)—a chimera of the homodimeric macrocyclic hydroxamate siderophores putrebactin and bisucaberin . In a disc‐diffusion assay on agar, avaroferrin (50 nmol) led to the formation of a zone with inhibited swarming motility of V. alginolyticus whereas the homodimeric siderophores were considerably less active .…”
Section: Interspecies Competition and The Microbiotamentioning
confidence: 99%
“…AvbD from S. algae B516 was cloned as previously established. [13] The proteins were recombinantly expressed in E. coli BL21. The proteins were purified from StrapTrap HP affinity column (GE Healthcare Bio-Sciences AB, Sweden) on an ¾KTA start protein purification system.…”
Section: Synthesis Of Hs[x]a and Hp[5]a: Hs[x]a And Hp[5]mentioning
confidence: 99%
“…This is particularly surprising since desferrioxamine is listed by the World Health Organization (WHO) as essential medicine for its use in treating iron overdose occurring during blood transfusionsa nd dialysis. NIS synthetases are non-modular,a nd do not have domain architecture, raising the question how these standalone enzymes have evolvedt og enerate different siderophores or could be engineered to produce novel compounds.T he type CN IS synthetases AvbD and DesD are closely related, yet AvbD produces as native metabolites the macrocyclic heterodimeric siderophore avaroferrin, as well as the homodimers putrebactin and bisucaberin, [13] whereas DesDp roduces the trimeric macrocycle desferrioxamineE (Scheme 1c)a sw ell as trimerice nd-capped linear desferrioxamine Ba nd other linear derivatives depending on upstream substrate N-acylation by DesC. [14] This difference makes AvbD and DesD ideal model systems to investigate the mechanism of oligomerization and macrocyclization by artificial substrates and investigate if mutationsc an tune substrate selectivity and siderophore production by this enzyme class.…”
Section: Introductionmentioning
confidence: 99%